2020
DOI: 10.3390/ijms21207760
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Derived Smoke Affects Biochemical Mechanism on Plant Growth and Seed Germination

Abstract: The role of plant-derived smoke, which is changed in mineral-nutrient status, in enhancing germination and post-germination was effectively established. The majority of plant species positively respond to plant-derived smoke in the enhancement of seed germination and plant growth. The stimulatory effect of plant-derived smoke on normally growing and stressed plants may help to reduce economic and human resources, which validates its candidature as a biostimulant. Plant-derived smoke potentially facilitates the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 138 publications
(144 reference statements)
0
25
0
1
Order By: Relevance
“…It has been demonstrated that PDS plays a key role in the alleviation of abiotic stresses. Seed primed with PDS has been found to increase seed germination percentage and seedling fresh weight in salt-stressed maize [ 28 , 29 , 30 ]. Sapium sabiforum has shown improved tolerance to salt and osmotic stresses by increasing germination and post-germination growth in PDS [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that PDS plays a key role in the alleviation of abiotic stresses. Seed primed with PDS has been found to increase seed germination percentage and seedling fresh weight in salt-stressed maize [ 28 , 29 , 30 ]. Sapium sabiforum has shown improved tolerance to salt and osmotic stresses by increasing germination and post-germination growth in PDS [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The plant-derived smoke solution is a material for promoting plant growth/development and affects plant species from various habitats [ 6 ]. Plant-derived smoke positively affected the post-germination growth of rice [ 7 , 8 , 9 ], maize [ 10 ], chickpea [ 11 ], soybean [ 12 , 13 , 14 , 15 ], and wheat [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the post-germination of crops treated with the plant-derived smoke solution elucidated that its treatment affected not only the seed-germination stage but also the plant growth and development stages [ 17 ]. Butanolides, including karrikins and cyanohydrin, are the active compounds in the plant-derived smoke solution [ 6 ]. The functional mechanisms of plant-derived smoke in the seed-germination stage were clarified with the discovery of karrikin [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plant-derived smoke is material for promoting plant growth/development and affects plant species from various habitats [1]. Butanolides, including karrikins and cyanohydrin, are the active compounds in plant-derived smoke [1].…”
Section: Introductionmentioning
confidence: 99%
“…Plant-derived smoke is material for promoting plant growth/development and affects plant species from various habitats [1]. Butanolides, including karrikins and cyanohydrin, are the active compounds in plant-derived smoke [1]. Plant-derived smoke positively affected post-germination growth of rice [2][3][4], wheat [5], maize [6], soybean [7][8][9], and chickpea [10].…”
Section: Introductionmentioning
confidence: 99%